2015
DOI: 10.1002/jsfa.7353
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition and nutritional quality of deep sea growth sea cucumbers (Stichopus japonicus) from different origins

Abstract: DSG-SCs are a good source of collagen, polysaccharides (especially fucose), EAAs (especially leucine and threonine) and PUFAs (especially EPA and DHA). Dalian seems to be a promising origin to produce high-value sea cucumber with high PUFA, fucose, collagen and protein contents. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 43 publications
(69 reference statements)
2
22
0
Order By: Relevance
“…RTE-VS, the rehydrated products of RTE-V, also had significantly higher contents of basic components than those in RTE-T, except moisture (p < 0.05). The polysaccharide content in FC was 6.75 ± 0.59 g/100 g, which was in agreement with the results obtained by Gao et al (2016). The polysaccharide content in FC was 6.75 ± 0.59 g/100 g, which was in agreement with the results obtained by Gao et al (2016).…”
Section: Proximate Compositionsupporting
confidence: 91%
See 1 more Smart Citation
“…RTE-VS, the rehydrated products of RTE-V, also had significantly higher contents of basic components than those in RTE-T, except moisture (p < 0.05). The polysaccharide content in FC was 6.75 ± 0.59 g/100 g, which was in agreement with the results obtained by Gao et al (2016). The polysaccharide content in FC was 6.75 ± 0.59 g/100 g, which was in agreement with the results obtained by Gao et al (2016).…”
Section: Proximate Compositionsupporting
confidence: 91%
“…In China, approximately 28 of the 134 species of sea cucumber are considered edible (Zhang et al, 2016). The farmed A. japonicus is rich in proteins, minerals, and special bioactive substances such as polysaccharides (Gao et al, 2016). In recent years, sea cucumber Apostichpous japonicas has become the dominate species cultured in northern China, including in Liaoning and Shandong Provinces.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used as an ideal tonic food source and a functional food in China for a long time . It was reported that the body wall protein in S. japonicus made up approximately 70% of the total weight . These abundant proteins are a rich source for making high‐quality peptides.…”
Section: Introductionmentioning
confidence: 99%
“…In A. mollis, the ratio of essential amino acids to non-essential amino acids is relatively small (i.e. 0.3) compared to tropical sea cucumber species with ratios between 0.4 and 0.6, and when compared with the temperate C. frondosa and A. japonicus with ratios ranging from 0.3 to 0.7 [11][12][13]31]. Nonetheless, the high composition of essential amino acids in the collagen of A. mollis reflects the premium quality of protein from this species [13].…”
Section: Amino Acids In Sea Cucumbersmentioning
confidence: 99%
“…Collagen can comprise as much as 30% of the total protein in the body wall of sea cucumbers [10]. Another temperate species, Apostichopus japonicus, has been reported to contain more than ten times more collagen than measured in A. mollis [31]. The collagen fibres in sea cucumbers as observed in A. mollis are also responsible for the mechanical properties of the dermis and for the maintenance of the tissue integrity [10,13,20,21,32].…”
Section: Collagen In Sea Cucumbersmentioning
confidence: 99%